Cultural Identification, Acculturation, and Academic Experience Abroad: A Case of a Joint Faculty-Led Short-Term Study Abroad Program - Lee, Jeongyi; Negrelli, Kathryn (Journal of International Students, 2018)
The number of students expanding their academic programs to include learning experiences abroad has been steadily increasing over the past two decades. This study investigates the cultural identification of short-term study abroad participants and its influence on their acculturation process. By means of a widely used acculturation scale, it was found that there were statistically significant effects of cultural experiences on cultural identification, specifically decreases in cultural identification scores. Implications from this study suggest a deeper understanding of students’ ethnic identifications can be helpful in developing study abroad programs that promote the goals of student awareness, cultural sensitivity, and global competence.